Culture in the design of mHealth UI: An effort to increase acceptance among culturally specific groups - Alsswey, Ahmed Housni; Al-Samarraie, Hosam; El-Qirem, Fuad Ali; Alzahrani, Ahmed Ibrahim; Alfarraj, Osama (Electronic library, 2020)
Investigates the design of a mobile health (mHealth) application user interface (UI) based on Arabic culture. Argues that integrating certain cultural values of specific groups of users into the design of UI would increase their acceptance of the technology. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.